Young radicals : in the war for American ideals - McCarter, Jeremy, 1976- (Random House, 2017)
"What does it mean to live for your ideals...and to risk dying for them? This book tells the story of young American radicals who sensed a moment of unprecedented promise for American life--politically, socially, culturally--and struggled to bring it about, only to see a cataclysmic war sweep it away. Based on six years of extensive archival research, Jeremy McCarter's dramatic narrative brings to life the adventures of Randolph Bourne, a cerebral hunchbacked writer, Max Eastman, an activist editor, Walter Lippmann, a slippery political operative, Alice Paul, a trailblazing suffragette, and John Reed, a Communist journalist. It evokes the America they fought to create in the early 20th century, one that young radicals are still fighting to create in the 21st, through movements such as Occupy and Black Lives Matter"--